Women’s Empowerment in Action : Evidence from a Randomized Control Trial in Africa - Bandiera, Oriana; Buehren, Niklas; Burgess, Robin; Goldstein, Markus; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (World Bank, Washington, DC, 2017)
Women in developing countries are disempowered: high youth unemployment, early marriage and childbearing interact to limit their investments into human capital and enforce dependence on men. The authors evaluate a multi-faceted policy intervention attempting to jumpstart adolescent women’s empowerment in Uganda, a context in which 60 percent of the population are aged below twenty. The intervention aims to relax human capital constraints that adolescent girls face by simultaneously providing them vocational training and information on sex, reproduction and marriage. The authors find that four years post-intervention, adolescent girls in treated communities are 48 percent more likely to engage in income generating activities, an impact almost entirely driven by their greater engagement in self-employment. Teen pregnancy falls by 34 percent, and early entry into marriage/cohabitation falls by 62 percent. Strikingly, the share of girls reporting sex against their will drops by close to a third and aspired ages at which to marry and start childbearing move forward. The results highlight the potential of a multi-faceted program that provides skills transfers as a viable and cost-e¤ective policy intervention to improve the economic and social empowerment of adolescent girls over a four year horizon.